Proceedings of the 1st International Conference on Early Childhood and Primary Education (ECPE 2018) 2018
DOI: 10.2991/ecpe-18.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Errors in Elementary School: A Meta-Synthesis Study

Abstract: Understanding mathematical errors is important for improving learning. In order to map the pattern of studies related to the mathematical errors, this study used qualitative approach with systematic meta-synthesis method. Data collection conducted in this research using documentation techniques by reviewing and summarizing the results of similar research. The studies included in this research were generated from 5 theses of bachelor and master degree of elementary school major in Universitas Negeri Malang. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Several studies at the middle school and early high school levels have shown that many students have trouble learning mathematical concepts and procedures (Yetkin, 2003;Maguire, 2012;Sakinah Nuraini et al, 2018). The high rate of mathematical errors in schools reveals this struggle with mathematics among students (Elbrink, 2008;Lai, 2012;Riccomini, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies at the middle school and early high school levels have shown that many students have trouble learning mathematical concepts and procedures (Yetkin, 2003;Maguire, 2012;Sakinah Nuraini et al, 2018). The high rate of mathematical errors in schools reveals this struggle with mathematics among students (Elbrink, 2008;Lai, 2012;Riccomini, 2016).…”
Section: Introductionmentioning
confidence: 99%